Non involuting congenital hemangioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 25-day-old infant was first observed due to the presence of a vascular lesion of the right elbow. The baby was born at term and his family history was negative for similar lesions. The parents reported that the tumor was present since birth and provided us with the photographic proof (Fig. 1). The physical examination (Fig. 2) revealed a 7 cm in diameter, raised for 4 cm, gray-blue neoformation, with numerous telangiectasias and a peripheral paler rim, warmer than the surrounding tissues and of soft-elastic consistency. These data led to the diagnosis of congenital hemangioma. In the following months there was not a further growth. At 20 months of age (Fig. 3) the tumor did not undergone significant changes, there were still numerous telangiectasias, but the white peripheral rim was not visible. The evolution data led to the final diagnosis of non involuting congenital hemangioma.